Design and Development of Self-preserving and Preservative-free Herbal Liquid Oral Formulation - Hulikal Basavarajaiah Pushpalatha, Kumar Pramod, Ramachandran Sundaram, Ramakrishnan Shyam (Journal of Applied Pharmaceutical Science, 2015)
Microbial contamination is one of the major inevitable concerns associated with herbal liquid formulations, which may originate from herbal raw materials. Inclusion of preservatives in herbal liquid formulations has been of considerable value for many years. Anti-microbial preservatives are normally added to prevent microbial proliferation while the product on shelf and during in use conditions. The properties of these preservatives are due to certain functional groups, which are usually harmful to living cells and might therefore be associated with certain risks when used in humans and they are the leading causes of adverse reactions and have negative and potentially life threatening side effects, because they not only act on microorganism but may also interfere with human cells. In this study, we have made an effort to develop a preservative-free and self-preserving liquid oral formulation by understanding and applying alternative principles of preservation (approaches other than using preservatives) by taking Ashoka herb extract as a prototype. Our series of formulation trials using different vehicle systems, which reduce the water activity by controlling the pH and osmotic conditions successfully yielded a vehicle system that could be used for the manufacturing of stable preservative-free/self-preserving herbal liquid oral formulations. Ashoka formulations were found to be physically, chemically and microbiologically stable during the six months of accelerated stability studies.
Keywords: Ashoka,herbal liquid formulation,water activity,preservative-free,self-preserving,stability studies.